Positivism, science, and 'The Scientists' in Porfirian Mexico : a reappraisal - Priego, Natalia (Liverpool Latin American studies ;, 2016)
This innovative monograph is of major significance for not only students and academics undertaking research on the history of Mexico during the long dictatorship of Porfirio Díaz, but also scholars specializing in the history of ideas, philosophy and science. Unlike previous discussions of positivism in Latin America, this book presents a detailed analysis of the English thinker, Herbert Spenceru2019s original works as a necessary gateway into the discussion of the thinking of 'The Scientists'. Its principal purpose is to revisit the influential thesis of Leopoldo Zea which proposed that 'The Scientists' throughout this period were Spencerian positivists. This book offers a revisionist analysis of the original papers of 'The Scientists', Francisco Bulnes and Justo Sierra, as well as their political and philosophical ideas and activities. This analysis demonstrates that their eclectic discourses used the ideas of the American Social Darwinists, and those from Spencer, Darwin, August Comte, andother European writers, concluding that 'The Scientists' lacked a clear leader and had an ambivalent relationship with Díaz. It interprets 'The Scientists' not as 'heroes' or 'villains', but as men struggling to appropriate European philosophical advances into their quest to modernise Mexico.